1972
DOI: 10.1136/oem.29.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of pulmonary impairment in simple coal workers' pneumoconiosis to type of radiographic opacity

Abstract: coal workers' pneumoconiosis to type of radiographic opacity. From a group of 1 461 working coal miners who participated in an epidemiological study, 223 men with simple pneumoconiosis were selected on the basis of the type of small rounded opacity noted to be present in their chest films. No differences in spirometry or lung volumes were found between those with the micronodular (q) and those with pinhead (p) opacities. Twenty-five non-smoking miners with category 2 or 3 simple coal workers'pneumoconiosiswere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1972
1972
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Diffusing capacity for carbon monoxide was measured by the single breath technique (Ogilvie et al, 1957) modified by using residual volume obtained in the plethysmograph and analysing the gases in a gas chromatograph (Beckman Co., Fullerton, California, Model GC5A). Values obtained in 20 healthy men and 30 healthy women subjects in the ALFORD laboratory were used to predict the normal diffusing capacity in these subjects (Seaton, 1972;Seaton, Lapp, and Morgan, 1972).…”
Section: Methods'mentioning
confidence: 99%
“…Diffusing capacity for carbon monoxide was measured by the single breath technique (Ogilvie et al, 1957) modified by using residual volume obtained in the plethysmograph and analysing the gases in a gas chromatograph (Beckman Co., Fullerton, California, Model GC5A). Values obtained in 20 healthy men and 30 healthy women subjects in the ALFORD laboratory were used to predict the normal diffusing capacity in these subjects (Seaton, 1972;Seaton, Lapp, and Morgan, 1972).…”
Section: Methods'mentioning
confidence: 99%
“…Nevertheless, in a small proportion of coal miners' abnormal pulmonary function tests, airflow obstruction and changes in diffusing capacity were observed with macules (pea-size small opacities) (60). A 9-year follow-up study of coal miners with simple CWP (small rounded opacities) showed only a small fall in gas exchange (61).…”
Section: Respiratory Symptoms Ofcwpmentioning
confidence: 99%
“…Motley et al (1950) reported a decrease in VC and FEV, parameters in the micronodular stage of pneumoconiosis. Brasseur (1963) reported lower values of FVC and FEV, in cases suffering from p and q types of simple pneumoconiosis as compared to those having normal X-rays, while Sargent and Morgan (1980), Renzetti et al (1970), Seaton et al (1972), Ziskind et al (1976) and Gupta et al (1976) observed relatively normal ventilatory function in simple pneumoconiosis. Pulmonary function impairment in advanced (A,B ,C) categories of pneumoconiosis observed in the present study is consistent with the findings of Zhicheng (1986), Jones et al (1975), Gupta et al (1976) and Rastogi et al (1983).…”
Section: Discussionmentioning
confidence: 90%